THE IMPACT OF SOIL TEXTURE ON ITS CAPACITY TO ADSORP– DESORB Pb, Zn and Cd ADDED TO CALCAREOUS SOIL - Al- Obaidi, Hamdiay Sh. (Diyala Agricultural Sciences Journal, 2018)
One sample was collected form surface layer (0-20 cm) of a soil which classified under sub-group as Typic Argixerolls, from Penjwin region of Sulaymaniyah province. Some chemical, physical and mineralogical characteristics was investigated then mixed with a different amount of pure sand to get different proportions of sand, silt and clay. The adsorption capacity of Pb2+, Zn2+ and Cd2+ by these samples has been studied to calculate both k and Xm parameters of Langmuir equation. To assess the soil's ability to release Pb2+, Zn2+ and Cd2+, soil samples treated with 250 µg g-1 were incubated for two weeks, then the available fraction of these elements were extracted in three successive extractions. The concentration of Pb2+ and Zn2+ and Cd2+ by each step of extraction was measured by atomic absorption. Data indicate that the Xm values for Pb2+, Zn2+ and Cd2+ were decreased with increasing sand ratios in soil samples. Obtained values of Xm for lead, zinc and cadmium, respectively ranged from 36.9 - 130.5, 10.8 - 126.9 and 28.8 - 159.3 µg g-1 while the k values were decreased form: 0.10 - 0.60, 0.04 - 0.80 and 1.05 - 0.11 µg ml-1. The decline in Xm and k values were ascribed to the low activity of sand fraction compared with activity of silicate and carbonate minerals as well as the organic fraction. Desorption of Pb2+, Zn2+ and Cd2+ added in a level of 250 µg g-1 data indicated that most of the lead, zinc and cadmium added was subjected to adsorption and precipitation during the two weeks of incubation. Ratio of sorped amount of Pb2+, Zn2+ and Cd2+ was 97.81- 99.56, 96.32 - 97.89 and 96.32 - 99.91% of added concentration, indicating that the fixed amount decreased with increasing in sand fraction in soil samples. We can concluded from these values that these elements strongly sorped regardless the increase in available amount with increase in sand fraction. High fixation of these heavy metals ascribe to their interaction with silicate and carbonate minerals as well as the organic material.